Trust the lord with all your heart: the role of education the relationship between trust in God and well-being in later life - Upenieks, Laura (Mental health, religion & culture, 2023)
Trust is a primary component of faith and may be helpful for initiating, maintaining, and even repairing a relationship with God. In this study, we take up the task of expanding the empirical basis of trust in God and its relationship to well-being. Using a nationally representative sample of middle-aged and older adults from the United States, we examined whether trust in God is associated with well-being, and if this association may be conditioned by a key marker of socioeconomic status – education. Trust in God was associated with lower depressive symptoms and better self-rated health. Trust in God was more strongly associated with well-being for the less educated (high school education or less). We discuss the implications of our results for pastors and religious ministers noting the importance of trust in God as a religious construct, especially for less educated respondents.